Fractional Complex Transform and exp-Function Methods for Fractional Differential Equations - Bekir, Ahmet; Guner, Ozkan; Cevikel, Adem C. (HINDAWI PUBLISHING CORP, 2013)
The exp-function method is presented for finding the exact solutions of nonlinear fractional equations. New solutions are constructed in fractional complex transform to convert fractional differential equations into ordinary differential equations. The fractional derivatives are described in Jumarie's modified Riemann-Liouville sense. We apply the exp-function method to both the nonlinear time and space fractional differential equations. As a result, some new exact solutions for them are successfully established.
Keywords: NONLINEAR EVOLUTION-EQUATIONS; CAHN-HILLIARD EQUATION; VARIABLE-COEFFICIENTS; MATHEMATICAL PHYSICS; PERIODIC-SOLUTIONS; CALCULUS; MODELS; Mathematics